2014
DOI: 10.1128/jvi.01349-14
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus (EBV) Glycoprotein B Cytoplasmic C-Terminal Tail Domain Regulates the Energy Requirement for EBV-Induced Membrane Fusion

Abstract: The entry of enveloped viruses into host cells is preceded by membrane fusion, which in Epstein-Barr virus (EBV) is thought to be mediated by the refolding of glycoprotein B (gB) from a prefusion to a postfusion state. In our current studies, we characterized a gB C-terminal tail domain (CTD) mutant truncated at amino acid 843 (gB843). This truncation mutant is hyperfusogenic as monitored by syncytium formation and in a quantitative fusion assay and is dependent on gH/gL for fusion activity. gB843 can rescue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 52 publications
(106 reference statements)
2
33
0
Order By: Relevance
“…This is in agreement with data from a recent report in which a hyperfusogenic truncation mutant of EBV gB mediated fusion at levels well above those of WT gB even with reduced incubation times and temperatures (48). We (27) and others (48) have proposed that hyperfusogenic mutants either exist in an activated conformation or require less energy to achieve such a conformation. If so, they could potentially mediate fusion in the absence of gD or gH/gL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with data from a recent report in which a hyperfusogenic truncation mutant of EBV gB mediated fusion at levels well above those of WT gB even with reduced incubation times and temperatures (48). We (27) and others (48) have proposed that hyperfusogenic mutants either exist in an activated conformation or require less energy to achieve such a conformation. If so, they could potentially mediate fusion in the absence of gD or gH/gL.…”
Section: Discussionsupporting
confidence: 93%
“…A hyperfusogenic truncation mutant of EBV gB has been shown to achieve the same fusion levels as the WT with less gH/gL (48). We tested whether hyperfusogenic mutants of HSV-1 gB had the same ability by measuring cell-cell fusion in the presence of different amounts of transfected WT gH.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is growing evidence that the gB cytoplasmic domain is critical for membrane fusion (22,28,36). The conserved gBcyt lysine cluster was first recognized to have a role in membrane fusion in an in vitro cell-free cell-cell fusion assay study involving HSV-1 gBcyt (28).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cell fusion in transfection-based assays could be significantly enhanced by deleting the most C-terminal amino acids, including the predicted endocytosis motifs (33,(52)(53)(54)(55)(56). Although it was originally speculated that enhanced presence of gB at the plasma membrane increases cell-cell fusion, recent data showed that the degree of surface localization is not necessarily causally related to increased fusion (52).…”
Section: Fig 4 Gbmentioning
confidence: 99%